Pengaruh Hybrid Learning dan Motivasi Belajar Terhadap Keaktifan Siswa Di SMAK XYZ Jababeka [The Influence of Hybrid Learning and Learning Motivation on Students Activities at SMAK XYZ Jababeka] - Kusumaanggara, Tommy Betta; Purbojo, Rijanto (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2023)
Hybrid learning was held in response to the government's directive regarding steps to anticipate the Covid 19 outbreak. Public and private schools have begun to stop learning at school and begin to implement hybrid learning. Hybrid learning can reduce student learning motivation and student activity. This study aims to determine the influence of hybrid learning and learning motivation on student activity while at SMAK XYZ Jababeka. The subjects in this study are sixty-five students of class X and XI SMAK XYZ Jababeka. The research method used by the author is Path Analysis using a quantitative approach. The questionnaire research instruments used are to measure hybrid learning, learning motivation, and student activity. The results of this quantitative study show that hybrid learning affects student activity in learning, hybrid learning affects learning motivation, learning motivation affects student activity at SMAK XYZ Jababeka. So, it was concluded that hybrid learning influences activity, student learning motivation and learning motivation has an effect on student activity when conducting hybrid learning.